Game-theoretic analysis of blockchain-enabled subcontracting model in construction projects - Jong Han Yoon; Pardis Pishdad (Blockchain)
Blockchain-enabled subcontracting model has been developed to address the issue of bid shopping in construction projects. However, the impact of this blockchain application on the decision-making of project stakeholders and its economic outcomes has not been thoroughly examined. This study establishes a game-theoretic framework to evaluate the economic implications of stakeholders' behaviors in the construction project subcontracting process. Utilizing this framework, the study investigates how the blockchain-enabled subcontracting model influences stakeholders’ decision-making and economic outcomes when compared to the traditional subcontracting model. The findings of this examination indicate that the blockchain application can effectively reduce opportunistic behaviors, leading to mutually beneficial outcomes for the stakeholders. This outcome contributes to the existing knowledge by 1) elucidating the practical implications of blockchain-based subcontracting models in the construction industry, bridging the gap between new technological applications and industry practices, and 2) illustrating that blockchain technology promotes ethical decision-making among General Contractors (GC) and Subcontractors (Subs) during the subcontracting process, ultimately improving quality and profitability by reducing the risks of claims and disputes.